Compact Left-Handed Meta-Atom for S-, C- and Ku-Band Application - Md. Mehedi Hasan; Mohammad Rashed Iqbal Faruque; Mohammad Tariqul Islam (Applied Sciences, 2017)
A new compact left-handed meta-atom for S-, C- and Ku-band applications is presented in this paper. The proposed structure provides a wide bandwidth and exhibits left-handed characteristics at 0°, 90°, 180° and 270° (xy-axes) rotations. Besides, the left-handed characteristics and wide bandwidth of 1 × 2, 2 × 2, 3 × 3 and 4 × 4 arrays are also investigated at the above-mentioned rotation angles. In this study, the meta-atom is designed by creating splits at the outer and inner square-shaped ring resonators, and a metal arm is placed at the middle of the inner ring resonator. The arm is also connected to the upper and lower portions of the inner ring resonator, and later, the design appears as an I-shaped split ring resonator. The commercially available, finite integration technique (FIT)-based electromagnetic simulator CST Microwave Studio is used for design and simulation purposes. The measured data comply well with the simulated data of the unit cell for 1 × 2, 2 × 2, 3 × 3 and 4 × 4 arrays at every rotation angle. Owing to the effective medium ratio (EMR) of 8.50 at 0° and 180° rotations, the proposed meta-atom structure is compact in size. Moreover, due to the quality factor of 82, the designed meta-atom is flexible for high-performance antenna, filter and sensor applications. Therefore, the meta-atom integrated antenna shows multi frequency bands with the highest peak gain of 5 dBi, which is used as the long distance radio communication frequency.